Chinese blue days: a novel index and spatio-temporal variations - Su Wang; Gang Huang; Jintai Lin; Kaiming Hu; Lin Wang; Hainan Gong (Environmental Research Letters, 2019)
As part of the Blue-Sky Protection Campaign, we develop the Chinese Blue Days Index based on meteorology data from 385 stations in China during 1980–2014. This index is defined as the days with no rain, low cloud cover ≤75th percentile, and visibility ≥15 km at 2 pm. The spatio-temporal variations and possible driving factors of Chinese Blue Days (CBD) are further investigated, revealing a steadily rising rate of 1.6 day (d)/10 year (y) for the nationally averaged CBD during 1980–2014. At regional scales, the CBD exhibit an increasing trend >4 d/10 y in western China and a decreasing trend <−2 d/10 y in southeastern China, northwestern Xinjiang, and Qinghai. The minimum/maximum trends (−7.5/9.5 d/10 y) appear in Yangtze–Huai River Valley (YHRV)/southwestern China (SWC). The interannual variations in CBD are highly related to wind speed and windless days in YHRV but are closely associated with wind speed, rainless days and relative humidity in SWC, suggesting that the two regions are governed by different meteorological factors. Moreover, a dynamic adjustment method called partial least squares is used to remove the atmospheric circulation-related CBD trend. The residual CBD contributions for the total trend in summer and winter are 43.62% and 35.84% in YHRV and are 14.25% and 60.38% in SWC. The result indicates that considerable parts of the CBD trend are due to the change of atmospheric circulation in the two regions.